2020
DOI: 10.1158/0008-5472.can-19-1555
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 Promotes Endosome Recruitment of Hepatocyte Growth Factor Tyrosine Kinase Substrate to Suppress Tumor Proliferation

Abstract: ◥Beclin 1 has nonautophagic functions that include its ability to regulate endocytic receptor trafficking. However, the contribution of this function to tumor suppression is poorly understood. Here, we provide in vivo evidence that Beclin 1 suppresses tumor proliferation by regulating the endocytic trafficking and degradation of the EGFR and transferrin (TFR1) receptors. Beclin 1 promoted endosomal recruitment of hepatocyte growth factor tyrosine kinase substrate (HRS), which was necessary for sorting surface … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Consistent with this, our results show that ALOX12 is upregulated by NDV infection and ACSL4 activation is not necessary for NDV-induced ferroptosis (Figure S2G). Recent findings report AMPK-mediated beclin-1 phosphorylation induces ferroptosis (Matthew-Onabanjo et al, 2020;Song et al, 2018). However, Lee et al showed that PUFAs can be synthesized from the basic building block acetyl coenzyme A carboxylase and that AMPK suppresses ferroptosis by inhibiting ACC (Lee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, our results show that ALOX12 is upregulated by NDV infection and ACSL4 activation is not necessary for NDV-induced ferroptosis (Figure S2G). Recent findings report AMPK-mediated beclin-1 phosphorylation induces ferroptosis (Matthew-Onabanjo et al, 2020;Song et al, 2018). However, Lee et al showed that PUFAs can be synthesized from the basic building block acetyl coenzyme A carboxylase and that AMPK suppresses ferroptosis by inhibiting ACC (Lee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, beclin1 has been demonstrated to have non-autophagy functions such as regulation of endocytic receptor trafficking, apoptosis, and inflammation [ 90 ]. One study illustrated that beclin1 is able to regulate growth factor and nutrient receptors, thus inhibiting tumor proliferation [ 91 ]. Therefore, it is crucial to clarify the role that autophagy plays in CSCs and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, our results show that ALOX12 is upregulated by NDV infection and ACSL4 activation is not necessary for NDVinduced ferroptosis (data not shown). Recent findings report Ampk-mediated beclin-1 phosphorylation induces ferroptosis (Matthew-Onabanjo et al, 2020;Song et al, 2018). However, Lee et al showed that PUFAs can be synthesized from the basic building block acetyl coenzyme A carboxylase and that AMPK suppresses ferroptosis by inhibiting ACC.…”
Section: Discussionmentioning
confidence: 99%